BERAT LAHIR SEBAGAI FAKTOR PROGNOSIS UNTUK KEMATIAN NEONATAL DINI PADA BAYI BERAT LAHIR RENDAH - , Margono,S.Pd. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: About 38% of infant mortality occurs in those of less than 28 days old of which 75% is neonate mortality. LBW greatly contributes to the incidence of neonate mortality. Introduction to factors affecting neonate mortality in LBW infants can lead us to the management of optimum condition that minimizes neonate mortality rate in LBW infants. Objective: To identify risk of birth weight for the incidence of neonate mortality in LBW infants. Method: The study used historical cohort design, started from observing medical records of infants born at Bantul Hospital. Subjects of the study were LBW infants of less than 2,000 grams as exposed group and those between 2,000 and 2,499 as non exposed group selected according to inclusion and exclusion criteria. Data of the two groups were analyzed using RR statistical test with bivariate and multivariate analysis at confidence interval 95%. Result: During the period of the study there were 2,854 childbirths. There were 322 cases of LBW infants, 303 of them met criteria as samples. Incidence of LBW was 11.28%. There were 150 cases of infants at birth weight less than 2,000 grams as exposed group and 153 cases of infants at birth weight between 2,000 and 2,499 grams as non exposed group. Risk of neonate mortality in infants at birth weight less than 2,000 grams in preterm pregnancy increased 5.5 times (95% CI 1.39-21.77